Correction: Synthesis, crystal structure, and optical properties of fluorinated poly(pyrazole) ligands and in silico assessment of their affinity for volatile organic compounds. (27th July 2020) - Pedrini, Alessandro; Maspero, Angelo; Bracco, Silvia; Comotti, Angiolina; Galli, Simona; Marchiò, Luciano; Nardo, Luca; Penoni, Andrea; Scapinello, Luca; Sozzani, Piero; Vesco, Guglielmo; Mella, Massimo
Abstract : Correction for 'Synthesis, crystal structure, and optical properties of fluorinated poly(pyrazole) ligands and in silico assessment of their affinity for volatile organic compounds' by Alessandro Pedrini et al., New J. Chem., 2020, 44, 6443–6455, DOI: ; 10.1039/D0NJ00259C .